2014
DOI: 10.1371/journal.pone.0094424
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Diversity and Saccade Similarities: Culture Does Not Explain Saccade Latency Differences between Chinese and Caucasian Participants

Abstract: A central claim of cultural neuroscience is that the culture to which an individual belongs plays a key role in shaping basic cognitive processes and behaviours, including eye movement behaviour. We previously reported a robust difference in saccade behaviour between Chinese and Caucasian participants; Chinese participants are much more likely to execute low latency express saccades, in circumstances in which these are normally discouraged. To assess the extent to which this is the product of culture we compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 48 publications
0
28
2
Order By: Relevance
“…Horizontal eye movements were recorded binocularly with the same miniaturized head-mounted infrared saccadometer (Ober Consulting Ltd, Poland) used in previous studies[ 12 14 ]. This samples infrared reflectance signals at 1KHz, and low-pass filters them at 250 Hz with 12-bit resolution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal eye movements were recorded binocularly with the same miniaturized head-mounted infrared saccadometer (Ober Consulting Ltd, Poland) used in previous studies[ 12 14 ]. This samples infrared reflectance signals at 1KHz, and low-pass filters them at 250 Hz with 12-bit resolution.…”
Section: Methodsmentioning
confidence: 99%
“…In three separate studies we found that ESMs, defined by the proportion of ES executed in overlap conditions (>30%), make up a sizable proportion of Chinese participant groups (29% [ 12 ]; 22% [ 13 ]; 27%[ 14 ]), allowing us recruit them in larger numbers than previously and to study them in more detail. We confirmed that the phenomenon was the identical to that described in the earlier literature [ 12 , 13 ], and that the reason for the higher numbers of ESMs among Chinese participants was not due to some cultural influence [ 14 ]. We also found that although voluntary saccade performance in ESMs was compromised (we confirmed that they exhibited higher antisaccade error rates than non-ESM participants [ 13 ]) this was not due to a general deficit in oculomotor inhibitory control [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results provide no information about the cause or basis of these differences. Knox and Wolohan, 2014, suggest a distinction in oculomotor phenotype between Chinese and Caucasian [2], which suggests there could also be structural aspects of the iris which differ between populations that affect PSO. However, Amatya, Gong, and Knox, 2011 suggest any differences between populations may be the result of top-down executive functions [1].…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of the field of 'cultural neuroscience' new insights are emerging on the potential influence of cross-cultural factors on a wide range of measures of cognitive and low level behaviours. Whilst it is has been claimed that culture leads to differences in top-down executive functions [1,2], there is relative paucity of work on low level behavioural measures. Previous research has found a number of eye-tracking differences between different cultures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation